QUALITY OF LIFE OF PATIENTS UNDERGOING HEMODIALYSIS - P, Thenmozhi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to assess the quality of life (QOL) of patients undergoing hemodialysis (HD). The QOL of HD patients was found to be considerably impaired when compared to that of healthy individuals of the general population. The careful assessment of QOL helps to guide and achieve medical management to optimize their health experience. Methods: Cross-sectional research design was adopted with 130 samples who met the inclusion criteria to conduct the study in the dialysis unit, India. The instrument used for the study was to collect the data are demographic variable and kidney disease QOL - short form version 1.3 scale. Results: The mean total score of QOL was 48.73±22.65, the highest score was for dialysis staff encouragement scale (84.04±14.89) followed by social support scale (80.38±20.38) and quality of social interaction (71.52±18.74). However, role limitation caused by physical health problems, role limitation caused by emotional health, and burden of kidney disease scales yielded the lowest scores (22.12±18.05, 26.92±24.15, and 38.03±12.81, respectively). Conclusion: The present study findings concluded that patients on HD were not having adequate QOL in all domains except patient satisfaction due to changes in the physiological, chemical changes occur in the kidney.